Pengaruh Transformasi Digital terhadap Produktifitas dan Keunggulan Kompetitif UMKM Madu Harrumi - Robi Santoso; Reni Diah Setiowati; Riski Eka Lestari; Ilham Setio Wibowo; Laila Khairun Nisa (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
The development of digital transformation plays a crucial role in improving sales performance and competitiveness of MSME businesses in the modern era. This study aims to analyze the effect of digital transformation on sales efficiency and competitive advantage of Harrumi Honey MSMEs. The study population included 100 honey business actors, with samples determined using the Slovin formula (n = N / (1 + Ne²)) at a margin of error of 10%, resulting in 50 respondents. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) to test the relationship between variables. The results showed that digital transformation had a significant effect on increasing sales and competitive advantage of Harrumi Honey MSMEs. The application of digital technology, such as online marketing, digital transactions, and data management, also strengthened operational efficiency and business competitiveness. This study recommends the adoption of digital transformation as a whole to support the growth of MSMEs in the agribusiness sector.